Systematic review of classification systems for locally recurrent rectal cancer. Issue 3 (8th April 2021) - Rokan, Z; Simillis, C; Kontovounisios, C; Moran, B J; Tekkis, P; Brown, G
Abstract: Background: Classification of pelvic local recurrence (LR) after surgery for primary rectal cancer is not currently standardized and optimal imaging is required to categorize anatomical site and plan treatment in patients with LR. The aim of this review was to evaluate the systems used to classify locally recurrent rectal cancer (LRRC) and the relevant published outcomes. Methods: A systematic review of the literature prior to April 2020 was performed through electronic searches of the Science Citation Index Expanded, EMBASE, MEDLINE and CENTRAL databases. The primary outcome was to review the classifications currently in use; the secondary outcome was the extraction of relevant information provided by these classification systems including prognosis, anatomy and prediction of R0 after surgery. Results: A total of 21 out of 58 eligible studies, classifying LR in 2086 patients, were reviewed. Studies used at least one of the following eight classification systems proposed by institutions or institutional groups (Mayo Clinic, Memorial Sloan-Kettering – original and modified, Royal Marsden and Leeds) or authors (Yamada, Hruby and Kusters). Negative survival outcomes were associated with increased pelvic fixity, associated symptoms of LR, lateral compared with central LR and involvement of three or more pelvic compartments. A total of seven studies used MRI with specifically defined anatomical compartments to classify LR. Conclusion: This review highlights the various imaging systems in use to classify LRRC and some of the prognostic indicators for survival and oncological clearance based on these systems. Implementation of an agreed classification system to document pelvic LR consistently should provide more detailed information on anatomical site of recurrence, burden of disease and standards for comparative outcome assessment.